As concepções de função de Frege e Russell: um estudo de caso em filosofia e história da matemática - Gomes, Rodrigo Rafael [UNESP] (2015)
This work presents a case study about the conceptual and methodological development of Mathematics by the examination and comparison of function conceptions in the thinking of Gottlob Frege and Bertrand Russell. Particularly, we discuss the fregean extension of mathematical idea of function, the russellian notion of propositional function and their philosophical assumptions and implications. The basis for this study is a analisys of the authors' books on the foundations of Mathematics and some other authors' writings, included among these some posthumous publications. From this analisys we conclude that the comprehensive function concept of Frege and the Russell's propositional function are both generalizations of an important acquisition of mathematical thought, namely the idea of function, and that the conceptography, the type theory and the theory of descriptions, in turn, constitute the methodical exploration of what these generalizations imply. Finally, we conclude that, though there are expressives differences between the function conceptions of Frege and Russell, a pattern of rigour associated with more wide reflections on the nature of meaning emerges from their investigations of the concept of function: the fregian function and the propositional function are the entities that participate of their respective meaning relations and whose nature is explained by these relations